INDEKS ERITROSIT PADA PRE EKLAMPSI - Nathalya Dwi Kartika Sari; Hartatiek Nila; Ersalina Nidianti; Widya Novita Sari (LPPM Universitas Abdurrab, 2025)
Hypertension in pregnancy ranks as the top cause of death in Indonesia with a value of 33%. Systemic inflammation can be measured using various biochemical and hematological parameters. Preeclampsia (PE) is a complication due to pregnancy that has dangerous risks. Preeclampsia is characterized by high blood pressure and proteinuria. This condition generally appears when the gestational age reaches 20 weeks, is associated with placental hypoperfusion which is the main cause of fetal growth restriction and in severe cases develops into multi-organ dysfunction and even death of the mother and fetus. The aim of this research is to determine the Erythrocyte Index in pregnancies with preeclampsia. The research method used a cross sectional method obtained from medical record data for 1 year (August 2022 to August 2023) from complete blood tests (erythrocyte index) of normal pregnancies and preeclampsia pregnancies carried out at RSI Surabaya A Yani. This research was conducted on pregnant women with preeclampsia and healthy pregnant women at the RSI Surabaya A Yani obstetrics clinic